Unknown/enigmatic functions of extracellular ASC. Issue 4 (22nd June 2021) - de Souza, Jean Gabriel; Starobinas, Nancy; Ibañez, Olga Celia Martinez
Abstract: Apoptosis‐associated speck‐like protein containing a caspase recruit domain (ASC), encoded by PYCARD gene, is a 22 kDa small molecule, which aggregates into ASC specks during inflammasome activation. ASC protein is an adaptor protein present in several inflammasome complexes that performs several intra‐ and extracellular functions, in monomeric form or as ASC specks, during physiological and pathological processes related to inflammation and adaptive immunity. Extracellular ASC specks (eASC specks) released during cell death by pyroptosis can contribute as a danger signal to the propagation of inflammation via phagocytosis and activation of surrounding cells. ASC specks are found in the circulation of patients with chronic inflammatory diseases and have been considered as relevant blood biomarkers of inflammation. eASC amplifies the inflammatory signal, may induce the production of autoantibodies, transports molecules that bind to this complex, contributing to the generation of antibodies, and can induce the maturation of cytokines promoting the modelling of the adaptive immunity. Although several advances have been registered in the last 21 years, there are numerous unknown or enigmatic gaps in the understanding of the role of eASC specks in the organism. Here, we provide an overview about the ASC protein focusing on the probable roles of eASC specks in several diseases, up to the most recent studies concerning COVID‐19. Abstract : We provide an overview about the ASC protein focusing on the probable roles of extracellular ASC specks in several diseases, up to the most recent studies concerning COVID‐19.